Fluctuating asymmetry in Apis mellifera (Hymenoptera: Apidae) as bioindicator of anthropogenic environments - Andrade Nunes, Lorena (2015)
The successful distribution of A. mellifera is due to their ability to adjust to seasonal variations, considerable control over their internal physical environment and exploration of different resources. However, their populations have experienced different forms and levels of environmental pressure. This research aimed to verify the phenotypic plasticity in both size and shape of wings in A. mellifera using fluctuating asymmetry, based on geometric morphometrics from apiaries located in sites with high and low levels of anthropization. We sampled 16 locations throughout all five geographic regions of Brazil. At each site, samples were collected from 20 beehives installed in apiaries: 10 installed near high anthropogenic environments (Cassilândia - MS, Fortaleza - CE, Maringá - PR, Aquidauana - MS, Rolim de Moura - RO, Riachuelo - SE, Ubiratã - PR and Piracicaba - SP), and 10 in sites with low levels of human disturbance (Cassilândia - MS, Itapiúna CE, União da Vitória - PR, Aquidauana - MS, Rolim de Moura - RO, Pacatuba - SE, Erval Seco - RS, Rio Claro - SP). A sample of 10 individuals was taken in each hive, totaling 200 per location, for a total of 1 600 individuals. We used fluctuating asymmetry (FA) in size and shape of the forewing through geometric morphometrics. The FA analysis was conducted in order to check bilateral differences. The indexes of size and shape were submitted to analysis of variance (ANOVA), where the characters evaluated were used as factors to verify the size and shape differences. The results indicated an asymmetry on the shape of the wing (P < 0.001) but no asymmetry was observed on wing size. Considering FA as an environmental response and high and low impacted areas as a fixed factor, we observed significant differences (P < 0.05). The results for the wing shape in A. mellifera demonstrated that this feature undergoes more variation during ontogeny compared to the variation in size. We concluded that bee samples collected from colonies with higher levels of human disturbance had higher wing-shape asymmetry; the variation of fluctuating asymmetry in the wing shape of honeybees can be used as an indicator of the degree of environmental anthropization.